Integrating clinical and research training in child psychiatry: fifteen-year outcomes of a federally supported program - Amanda Calhoun; Michael H. Bloch; Dorothy Stubbe; James F. Leckman; Andrés Martin (BMC, 2020)
Abstract Background The Albert J. Solnit Integrated Training Program (AJSP) is an educational initiative designed to prepare physician-scientists for independent careers in the investigation and treatment of childhood psychiatric disorders. Methods We compared fifteen cohorts (each representing a consecutive year of matriculation) of AJSP trainees and graduates (n = 30) to peers who were comparably ranked in our original match lists but ultimately pursued residency programs elsewhere (n = 60). Outcomes of interest between the two groups included professional affiliation, as measured by: (1) membership in the American Academy of Child and Adolescent Psychiatry (AACAP); and (2) certification by the American Board of Psychiatry and Neurology (ABPN), as well as three domains of research productivity: (1) Competitive awards received from AACAP; (2) Publication-related metrics derived from the National Library of Medicine (NLM); and (3) Federal grant funding from the National Institutes of Health (NIH). Results AJSP participants were more commonly affiliated with AACAP and board certified in CAP. AJSP graduates and trainees outperformed their control group peers in several research outcomes: (1) Receipt of AACAP awards and number of awards per recipient were higher, and time to first award shorter in the AJSP than in the control group; (2) AJSP participants had more publications in PubMed, more first-authored publications, a higher h-index, and a shorter time to first publication than participants in the control group; and (3) NIH K- or R-series funding success rate was higher among AJSP participants (p < 0.05 for all comparisons). Conclusions A program designed to support the development of clinician-scientists specifically dedicated to childhood mental health needs has been successful in fostering scientific creativity, productivity and independence. The expansion and replication of similar training initiatives will be an in important step forward to address the high level of morbidity and mortality associated with child and adolescent psychiatric disorders.